Losch's Theorem on Hexagonal Market Areas - John M. Hartwick (Queen's University, Department of Economics, 1970)
In his classic work, The Economics of Location, August Losch claimed to have proved that the free entry of firms to a market in two dimensional geographic space characterized by uniform quality throughout its area would result in hexagon-shaped market areas.
Keywords: 330